Factors Influencing English-majored Freshmen’s Speaking Performance at Ho Chi Minh City University of Food Industry - Ly, Khanh Cong (Journal of English Language Teaching and Applied Linguistics, 2021)
It has been commonly recognized that many Vietnamese students encounter difficulties in communicating and speaking the English language. This study aims to explore the problems influencing university students’ performance in learning English speaking skills. The author carried out this research by surveying 178 English-majored freshmen at Ho Chi Minh City University of Food Industry. The findings from the analyzed quantitative data revealed that the respondents’ difficulties mainly came from internal factors. The internal factors were categorized into five main aspects: overuse of L1, weak listening and pronunciation, lack of topical knowledge and ideas, shyness and nervousness, and fear of mistakes and criticism. Some other external factors having less impact on the students’ speaking performance involved practicing time, the content of the topics, IELTS-oriented speaking tests, and lecturers’ support. This study was expected to help students overcome their internal problems and suggest some recommendations to minimize the undesirable effects of negative factors.